Asuhan Keperawatan Keluarga Pada Tahap Perkembangan Keluarga Dengan Anak Usia Sekolah Yang Menderita Hipertensi Dengan Tindakan Pendidikan Kesehatan Menggunakan Edukasi Booklet Dan Minum Rebusan Air Daun Salam - Lilis Rusfitasari; Rina Puspita Sari; M. Hasan Basri; Alfika Safitri (An-Najat, 2023)
Hypertension is often called the "silent killer" because it rarely shows signs and if it is suffered for a long time it can cause various complications. Hypertension requires appropriate treatment, both from a pharmacological and non-pharmacological perspective. Many non-pharmacological therapies have been developed abroad and are complementary interventions that can be used as a substitute for conventional medicine. Bay leaves contain flavonoids which function as antioxidants which can prevent oxidation of body cells. The content of flavonoids in bay leaves can be used to prevent hypertension. was to determine the effect of giving bay leaf decoction to changes in blood pressure in hypertensive patients in Kampung Bayur. of using boiled water bay leaves. By boiling with about 300 ml of water boiled for 15 minutes. After boiling in the filter and then ready to be consumed every day per 2 cups. In bay leaves there are compounds contained in bay leaves consisting of flavonoids, tannins, essential oils, eugenol, which can have an effect on reducing blood pressure. of this study was the Priuk Jaya family in July 11-15, the independent variable was giving boiled bay leaves and the dependent variable was changes in blood pressure. is that there is an effect of giving boiled bay leaf water to changes in blood pressure in hypertensive patients in Bayur Village, Periuk Jaya Health Center.